Haymarket Square and Washington Street intersection, ca. 1910 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southwest of the Haymarket Square and Washington Street intersection. 1 Washington Street is included in the center of the photograph. The building's north elevation faces Haymarket Square and is included in the right half of the photograph, while its east-northeast elevation lines Washington Street and is included in the left half of the photograph. Signage and awnings adorn the buildings included in the image. Pedestrians, a horse-drawn wagon and electricity poles and lines fill Haymarket Square. 8 x 10 1/8 Photographs